2019
DOI: 10.17576/geo-2019-1504-21
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Ecological Assets of Tunas Mekar Project’s Graduate Entrepreneurs

Abstract: Entrepreneurship has been one of the alternatives in overcoming the unemployment rate among the youths that graduated from the higher learning institutions in Malaysia. Various efforts and policies have been developed to increase the participation of graduates in the entrepreneurial field. Nevertheless, statistics show that the participation of graduates in this field is still unsatisfactory. There are two youth development assets that influence the ability of graduates to start a business, known as the indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Most researchers suggest entrepreneurship as one of the best solutions to overcome the problem of unemployment among graduates in Asian (Li et al, 2021;Zhou et al, 2021;Lu et al 2021;Mei et al, 2020;Lu et al, 2021;Yuan et al, 2020). One of the best ways to reduce the high unemployment rate among graduates is to start their own business (Kamaruddin et al, 2019). University entrepreneurship support programmes positively affects entrepreneurial attitude, entrepreneurial self-efficacy and entrepreneurial intention for more students to become entrepreneurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most researchers suggest entrepreneurship as one of the best solutions to overcome the problem of unemployment among graduates in Asian (Li et al, 2021;Zhou et al, 2021;Lu et al 2021;Mei et al, 2020;Lu et al, 2021;Yuan et al, 2020). One of the best ways to reduce the high unemployment rate among graduates is to start their own business (Kamaruddin et al, 2019). University entrepreneurship support programmes positively affects entrepreneurial attitude, entrepreneurial self-efficacy and entrepreneurial intention for more students to become entrepreneurs.…”
Section: Discussionmentioning
confidence: 99%
“…Graduate entrepreneurs had higher career satisfaction than graduate employees although they have more work commitments than graduate workers. Entrepreneurship also has been one of the options for combating the high unemployment rate among Malaysian graduates (Kamaruddin, Mauzud & Zin, 2019). Despite the different initiatives and policies implemented, statistics revealed that graduate involvement in this subject is still poor.…”
Section: Knowledge Experience and Skills Developmentmentioning
confidence: 99%